Schadenfreude Keagamaan di Kalangan Netizen Indonesia: Penghalang Tak Kasat Mata bagi Pluralisme dan Multikulturalisme di Indonesia - Awliya Rahmi; Delami; Wahyudi; Khairunnisa Islami (Diwan: Jurnal Bahasa dan Sastra Arab, 2022)
This research aims to examine the form of religious schadenfreude reflected on written comments on news. The data in this study were the documentation of comments on national and international news posted on the Youtube channel of national online news portal such as Tribun, Kompas and Liputan 6. It was found that religious Schadenfreude among Indonesian netizens exists in two major situations: Inter-religious relationship and within the religion itself. This phenomenon occurs in an empathetic situation in the form of religious stereotyping, trash-talking other religions and beliefs, the satisfaction of other’s misfortune. To conclude, the religious schadenfreude phenomenon among Indonesian netizens more likely occurs because society focus on the difference exists within the community. Therefore, promoting the beauty of religious diversity is required to eliminate antipathy and provide another perspective on pluralism and multiculturalism.